Collagen with simvastatin promotes cell metabolism in osteoblast-like SaOS-2 cells - Thanga Kumaran Suthanthiran; Sugumari Elavarasu; Devisree Naveen; Umamaheswari Nagarathinam; K V Arun; N Srinivasan (Wolters Kluwer Medknow Publications, 2012)
Background: Simvastatin (SMV) is one of the cholesterol-lowering pharmacological drugs. Recent studies demonstrate that it has a bone stimulatory effect. The present study was designed to investigate the effect of SMV along with collagen membrane on osteoblast-like SaOS-2 cells and also to standardize the dosage of SMV to be incorporated into the collagen membrane to achieve regeneration. Materials and Methods: SMV at doses of 0.5, 1, 1.5, and 2 mg was incorporated into the collagen membrane and cell metabolism was assessed by (3-[4,5-dimethylthiazolyl-2]-2,5-diphenyltetrazolium bromide) (MTT) assay for 24 h. Results: SMV enhanced cell metabolism dose dependently at 24-h time and the maximum effect was obtained at a concentration of 1.5 mg of SMV. Conclusion: These results indicate that collagen with 1.5 mg SMV exhibits positive effect on cell metabolism of human osteoblast-like SaOS-2 cells.